2019
DOI: 10.24263/2304-974x-2019-8-3-10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrocolloids on some properties of dough and quality of gluten-free bread enriched with whey protein concentrate

Abstract: Introduction. The effect of hydrocolloids (xanthan gum and guar gum) on dough properties and the quality of gluten-free bread from rice and corn flour enriched with whey protein concentrate was studied. Materials and methods. For the preparation of the whey protein concentrate it was used a laboratory system with a removable flat membrane module, equipped with a 25 kDa polyacrilonitrile ultrafiltration membrane. Dough consistency was measured by degree of immersion, using automatic penetrometer. Results and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…On the contrary, the increase in the XG concentration led to a decrease the Specific volume, which may be attributed to the high viscosity of XG which led to a weak ability of gas to expand inside the dough. These results are in good agreement with that reported by Chochkov et al, (2019) who referred to the negative impact of xanthan gum quantity increase on bread volume. Likewise, Mandala (2005) reported that Xanthan gum decreased loaf volume depending on the dose.…”
Section: Effect Of Gum Concentration On Specific Volume and Tpa Param...supporting
confidence: 93%
“…On the contrary, the increase in the XG concentration led to a decrease the Specific volume, which may be attributed to the high viscosity of XG which led to a weak ability of gas to expand inside the dough. These results are in good agreement with that reported by Chochkov et al, (2019) who referred to the negative impact of xanthan gum quantity increase on bread volume. Likewise, Mandala (2005) reported that Xanthan gum decreased loaf volume depending on the dose.…”
Section: Effect Of Gum Concentration On Specific Volume and Tpa Param...supporting
confidence: 93%
“…Lazaridou et al (2007) found that increasing level of xanthan up to 1% increases the crumb porosity, but increasing the gum level up to 2% has an adverse effect. However, previous researches have shown that gums could have positive or negative effects on the texture of the product depending on the structure and reaction with other ingredients in the bread formulation (Chochkov et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…All supported data are presented in the manuscript references section, for example: https://doi.org/10.1016/j.jff.2020.104065; https://doi.org/10.1111/1541-4337.12021; https://doi.org/10.1081/JFP-100105198; https://doi.org/10.3390/foods10050920. Alvarez‐Jubete et al (2010), Liu et al (2019), Arendt, Bello (2018), Lazaridou et al (2007), Chochkov Zlateva, Dushkova (2019), Mir et al (2016), Liu, Chen, Xu (2019), Piga et al (2021), Kittisuban et al (2014), Nunes et al (2009), Lazaridou et al (2007), Cai, Sun, Corke (2005), Ahlborn, Pike, Hendrix, Hess, Huber (2005), Moore, Heinbockel, Dockery, Ulmer, Arendt (2006), Lazaridou et al (2007), Gallagher, Gormley, Arendt (2004), Lazaridou et al (2007); Gamel et al (2006).…”
Section: Data Availability Statementmentioning
confidence: 99%